Crisis Communication Strategy PT. PLN (Persero) in Responding to Electric Blackout in Jakarta in 2019 - Istikhana Nurulhuda; Maulina Pia Wulandari; Bambang Dwi Prasetyo (International Journal of Science and Society, 2022)
Electricity is a primary need for people in the world, including Indonesia. PT. PLN (Persero) is the only electric company in Indonesia that provides electricity. The electricity blackout that occurred on August 4, 2019 in Jakarta as well as in several areas in West Java, Banten and Central Java paralyzed residents' activities, public services and industry. Using descriptive qualitative methods based on Situational Crisis Communication Theory (SCCT) with data collected through documents in the form of news related to the electricity blackout, this study tries to identify and describe how the Public Relations of PT. PLN (Persero) as a company that provides electricity uses a strategy to manage and deal with the crisis. The results of this study indicate that the Public Relations of PT. PLN (Persero) uses a combination of primary crisis response strategies between a reduction strategy (minimized) and a rebuild strategy (rebuild). In addition, they also use a secondary crisis response strategy in the form of a boosting strategy and a victim strategy.